Perceptions and behavioural intentions on airline safety among degree students after flight tragedies / Norita Mina Seli - Seli, Norita Mina (2015)
This study aimed to determine perceptions of safety after flight tragedies among degree students in UiTM, Campus 1 Kota Samarahan. There have four dimensions of perception of safety such as experiences, trustworthiness, reputation and tangible that affect the behavioural intention after flight tragedies. The result revealed that the reputation dimension of perception was the most important in this study. The relationship between perceptions and behavioural intentions on airline safety was also investigated. The perceptions of safety have a significantly positive relationship especially tangible dimension with behavloural intentions. In addition, in this study also provides recommendations to improve airline safety. In this study, 285 degree student respondents were selected to answer the questionnaires.